Neonatal Surgical Morbidity and Mortality at a Single Tertiary Center in a Low- and Middle-Income Country: A Retrospective Study of Clinical Outcomes - Hasan, Md Samiul; Islam, Nazmul; Mitul, Ashrarur Rahman (Frontiers in Surgery, 2022)
The limitations in the LMICs, both logistic & financial are the greatest challenges deferring the improvement in neonatal & pediatric surgical outcomes needs to be addressed with global collaboration with the advances places & international bodies. Data sharing the real picture of the deterring factors will help mitigate these challenges hopefully.